2010
DOI: 10.7196/samj.3462
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyhaemoglobin levels in water-pipe and cigarette smokers

Abstract: Water-pipes (hookah, narghile, shisha, goza, hubble bubble and in South Africa hubbly-bubbly) have been used to smoke tobacco for more than 400 years. Traditionally in the Middle East water-pipe smoking has been the habit of older men, but it is increasing in popularity worldwide, especially among students, other young people and children. 1 The popularity of water-pipe smoking appears to be based on its social nature and the assumption that its effects are less harmful than those of cigarette smoking.2 The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…WPS acutely leads to a marked CO inhalation and increased carboxyhaemoglobin (COHb) or exhaled CO when compared to cigarette smokers 17 35–37 and non-smokers. 36–38 An acute increase in CO levels (exhaled CO or COHb) is demonstrated in smokers following a timed WPS session 8 10 11 13–18 39–42 after exiting WP cafés 43 or compared to non-WP cafés, 44 and among passive smokers.…”
Section: Resultsmentioning
confidence: 99%
“…WPS acutely leads to a marked CO inhalation and increased carboxyhaemoglobin (COHb) or exhaled CO when compared to cigarette smokers 17 35–37 and non-smokers. 36–38 An acute increase in CO levels (exhaled CO or COHb) is demonstrated in smokers following a timed WPS session 8 10 11 13–18 39–42 after exiting WP cafés 43 or compared to non-WP cafés, 44 and among passive smokers.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that health professionals, including medical students, are generally perceived as role models in many societies, the finding of prevalent use of water pipe although not daily still poses a concern to public health efforts for tobacco control especially because water pipe smokers do not consider the practice harmful (Hammal et al, 2008). This belief persists despite the fact that recent studies both in South Africa and elsewhere have demonstrated significant adverse health effects associated with water pipe smoking (Maziak, Ward, Soweid, & Eissenberg, 2004;Theron, Schultz, Ker, & Falzone, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among United States college students pastmonth use is now reported between 10% and 20%, and even 7% of 12 th grade students report past-month waterpipe use [1]. Tobacco waterpipes, also known as hookahs, shishas, or narghiles, vary in composition by culture, but involve passing smoke through water and usually placing charcoal on top of a tobacco-filled pipe head [3,4]. Since the smoke in a waterpipe passes through water before inhalation by the user, and because the most popular type of waterpipe tobacco, maassel, is often fruit-flavored, waterpipes are often perceived to be less dangerous than cigarettes [1,4].…”
Section: Introductionmentioning
confidence: 98%